2015
DOI: 10.1007/s00726-015-2105-z
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine stimulates protein synthesis in enterocytes independently of glutathione synthesis

Abstract: Dietary supplementation with N-acetylcysteine (NAC) has been reported to improve intestinal health and treat gastrointestinal diseases. However, the underlying mechanisms are not fully understood. According to previous reports, NAC was thought to exert its effect through glutathione synthesis. This study tested the hypothesis that NAC enhances enterocyte growth and protein synthesis independently of cellular glutathione synthesis. Intestinal porcine epithelial cells were cultured for 3 days in Dulbecco's modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…These data indicate that H 2 O 2 induces mitochondrial ROS production and then leads to DNA damage in IPEC-J2 cells. The report by Yi et al indicated that NAC increased the growth of IPEC-1 cells and suggested that NAC at low concentrations (<1 mM) could stimulate cell growth [20]. In line with these results, this experiment showed that addition of NAC at 500–1000  μ M to 100  μ M H 2 O 2 treatment increased the cell viability.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data indicate that H 2 O 2 induces mitochondrial ROS production and then leads to DNA damage in IPEC-J2 cells. The report by Yi et al indicated that NAC increased the growth of IPEC-1 cells and suggested that NAC at low concentrations (<1 mM) could stimulate cell growth [20]. In line with these results, this experiment showed that addition of NAC at 500–1000  μ M to 100  μ M H 2 O 2 treatment increased the cell viability.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, supplement of NAC has been reported to improve growth performance and energy status, reduce inflammation, and ameliorate tissue damage [12]. Recently, Yi et al have found that NAC could stimulate protein synthesis and inhibit proteolysis in IPEC-1 cells [20]. In the present study, we found that NAC could not only ameliorate H 2 O 2 -induced cell growth inhibition, but also attenuate mitochondrial dysfunction in H 2 O 2 -treated cells.…”
Section: Discussionsupporting
confidence: 73%
“…Total RNA was quantified using the NanoDrop ® ND-1000A UV-VIS spectrophotometer (Thermo Scientific, Wilmington, DE, USA) at an OD of 260 nm, and its purity was assessed by determining the OD260/OD280 ratio. All of the samples had an OD260/OD280 ratio above 1.8 corresponding to 90–100% pure nucleic acids [ 21 , 38 ]. Meanwhile, RNA integrity in each sample was determined using 1% denatured agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…In a cell culture study using PC12 cells and sympathetic neurons deprived of neuotrophic factors, NAC supplementation was able to promote cell survival using a transcriptiondependent mechanism (Yan et al, 1995). Similarly, the results of a gene expression study in enterocytes suggested that NAC also increases protein synthesis (Yi et al, 2016). However, the role of NAC in protein homeostasis extends beyond protein synthesis to include protection against toxicity-induced protein degradation.…”
Section: Potential Therapies For Addiction May Influence Redox Statusmentioning
confidence: 99%